2019
DOI: 10.1029/2018jd030213
|View full text |Cite
|
Sign up to set email alerts
|

Regional Impacts of Urban Irrigation on Surface Heat Fluxes and Rainfall in Central Arizona

Abstract: Rapid urbanization over Phoenix has resulted in increased water consumption for maintenance of green spaces and heat stress mitigation. The hydrometeorological impact of urban irrigation is not well understood and is the principal objective of this study. Our results are based on high‐resolution numerical experiments using the Weather Research and Forecasting model. A simple irrigation scheme is implemented into the Weather Research and Forecasting model to represent changes in soil moisture due to irrigation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Average daily LST differences were reduced for the daytime (0800 to 1700 local time) from 3.2°C to 0.3°C over croplands and from 4.2°C to 1.4°C over urban areas. Furthermore, this shows that VIC-IRR can capture the evaporative cooling effect of irrigation in a means consistent with prior observations (Templeton et al 2018) and modeling work (Yang et al 2019). The evaporative cooling effect is also compared to the diurnal cycle of air temperature (T air ) obtained from the forcing product for each land cover type.…”
Section: Model Evaluations At Regional Scalesupporting
confidence: 79%
See 1 more Smart Citation
“…Average daily LST differences were reduced for the daytime (0800 to 1700 local time) from 3.2°C to 0.3°C over croplands and from 4.2°C to 1.4°C over urban areas. Furthermore, this shows that VIC-IRR can capture the evaporative cooling effect of irrigation in a means consistent with prior observations (Templeton et al 2018) and modeling work (Yang et al 2019). The evaporative cooling effect is also compared to the diurnal cycle of air temperature (T air ) obtained from the forcing product for each land cover type.…”
Section: Model Evaluations At Regional Scalesupporting
confidence: 79%
“…As such, a fruitful avenue of research is to incorporate remotely sensed products to determine the spatiotemporal patterns of vegetation conditions in evaluations of ICC in other regions with outdoor water use. The impacts of these dynamics should also be taken into account when considering the impact of irrigation on atmospheric conditions, for instance, through coupled land-atmosphere modeling (e.g., Xiang et al 2018;Yang et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This study utilizes a relatively simple calculation to determine the irrigation time and the fixed irrigation amount was used, which might be further refined in future studies. Second, the rapid urbanization might also result in an increased water consumption so as to maintain green space and mitigate heat stress (Y. Yang et al., 2019). Since this paper highlights the regional climate, urban irrigation was omitted, and we assumed that irrigation only happened on cropland.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the rapid urbanization might also result in an increased water consumption so as to maintain green space and mitigate heat stress (Y. Yang et al, 2019). Since this paper highlights the regional climate, urban irrigation was omitted, and we assumed that irrigation only happened on cropland.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Because a feasible reason is the exacerbation of convection by local UHI, especially at the start of the rainfall events. Yang et al (2019) analyzed the impacts of urban irrigation (i.e., irrigation for public greenspaces) on surface heat fluxes and precipitation in central Arizona using a high-resolution WRF model with or without an irrigation scheme. They found that urban irrigation had little impact on the average precipitation volume, but can significantly alter the spatial distribution of precipitation.…”
Section: Further the Process Understanding Of Extreme Precipitationmentioning
confidence: 99%